Germination dynamics of soybean cultivars in relation to common spring germinating weeds - Pålsson Andersson, Sofie (2021)
Soybeans are one the most traded crops in the world with main production areas in north and south America. Europe only produces 5 % of its domestic need for soybean. In the Nemoral zone of northern Europe no commercial cultivation of soybeans exists today. However, between 1940 -1960 there existed a breeding programme for soybeans in Sweden, but it never reached a commercial scale. Soybeans are interesting to introduce to Swedish organic farming for replacing imported soymeal in animal diets as well as for direct human consumption. To expand the soybean production further north more knowledge about soybeans maturity timing and temperature requirements during the major phenological stages needs to be acquired. An important trait for cultivation of soybeans in the Nemoral zone is capacity to germinate under the low temperatures which in this zone are common in spring. This thesis aims to study three germination dynamics parameters of soybeans; the base temperature for germination (Tb), growing degree days to 50 % germination (GDD50) and the maximum germination rate (b). Secondly, this study aims to investigate if there is an increased tolerance of germination under low temperatures for modern cultivars compared to historic Swedish cultivars. Thirdly, germination dynamic parameters of the most common weed species were studied with the aim to gather more information about weed-crop competition dynamics and possible implications on non-chemical weed management practices. In total 12 soybean cultivars and 10 weed species were studied. Germination experiments were carried out in climate chambers with 12 constant temperatures between 0 – 40 °C. Log logistic functions were used for estimation of the mentioned germination dynamic parameters. The results showed that there were significant differences regarding Tb, GDD50 and b between the studied soybean cultivars. There were also significant differences between modern cultivars and the historic cultivar ‘Fiskeby V’. Germination dynamic parameters of the studied weed species varied greatly. Based on the study results it can be concluded that a selection of soybean cultivars with contrasting germination dynamic parameters compared to the main weed species can help to optimise the timing of non-chemical weed management measures. Further it can be concluded that the studied parameters could be included in the future soybean breeding programs aiming for the adaptation of this crop to northern climates.